Teleology of Islamic Education: Reconstruction and Development of Holistic Educational Goals According to Muhammad Abduh - Rozaq Shohibul Ichsan; Muhammad Arif Syihabuddin (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
The backwardness of the Islamic world following the 18th-century stagnation spurred the emergence of reformist thought (tajdid). In this context, Muhammad Abduh emerged as a monumental figure who believed education was the primary instrument for the revival of the Muslim community, by holistically reconstructing its educational goals. This study aims to analyze and develop the concept of the goals of Islamic education according to Muhammad Abduh through library research with a philosophical approach. Operationally, these goals are implemented at three levels: (1) the elementary level to eradicate illiteracy and instill the foundations of religion; (2) the middle level to prepare responsible professionals; and (3) the high level to produce qualified leaders and educators. This goal concept is supported by an integral curriculum that combines religious knowledge (aqidah, fiqh, morals) with rational knowledge (logic, history, Arabic), as well as varied and anti-taqlid learning methods. Abduh's contributions to the development of Islamic educational theory are manifested through four pillars: purification (purification of teachings), institutional reform, reformulation of the ijtihad method, and the integration of religious knowledge with modern science. Thus, Abduh's concept of educational goals offers a progressive, contextual, and relevant framework to address the challenges of contemporary Islamic education, which is still struggling to eliminate the dichotomy of knowledge and integrate spiritual values ​​with intellectual progress.